The Phytohormones (iaa and ga3) produced by rhizosphere mushrooms in shallot (allium ascolonicum l). As a biostimulant - Hikmahwati, Hikmahwati; Fitrianti, Fitrianti; ilmi, Nur (Universitas Djuanda, 2023)
Plants that are symbiotic with microbes will produce phytohormones optimally, increasing plant tolerance to abiotic and biotic stress, including plant pathogens, so it is necessary to investigate the rhizosphere mushroom of onion plants in Enrekang regency and test the production of phytohormones (IAA and GA3) to determine its potential as a biostimulant in Shallot. This study used soil samples of shallot rhizosphere soil collected at the shallot farming center in Enrekang regency, as well as hormone isolation and testing at Hasanuddin University's laboratory of plant diseases. The results obtained are 20 isolates with IAA hormone production ranging from 0.125-3,609 mg / L, with isolate 3 and 7 having the highest IAA production, while GA3 hormone production ranges from 0.991-3,440 mg/L, GA3 production is released in isolates 8, 17, and 19. This demonstrates the high potential of rhizosphere mushrooms as biostimulants.